Atypical presentation of visceral leishmaniasis from non-endemic region - Sujeet Raina (Online Journal of Health & Allied Sciences, 2010)
A case of atypical and acute presentation of visceral leishmaniasis from non-endemic region, characterised by exudative pleural effusion and hepatitis is reported